A criminology of war? - McGarry, Ross (New horizons in criminology, 2019)
In recent years, the academic study of ‘war’ has gained renewed popularity in criminology. This book illustrates its long-standing engagement with this social phenomenon within the discipline. Foregrounding established criminological work addressing war and connecting it to a wide range of extant sociological literature, the authors present and further develop theoretical and conceptual ways of thinking critically about war. Providing a critique of mainstream criminology, the authors question whether a ‘criminology of war’ is possible, and if so, how this seemingly ‘new horizon’ of the discipline might be usefully informed by sociology.